(untitled) (Papeles, 2022)
Lithium has become a resource in great international demand in recent decades. It is estimated that in the so-called "lithium triangle" made up of the countries of the Southern Cone: Bolivia, Chile and Argentina, there are reserves equivalent to 85% of those existing on the planet, which positions these states in the attractive lithium market for more than two decades. The purpose of this article is to characterize the lithium policy in the province of Catamarca, Argentina, and the existing tensions in relation to its exploitation with actors of society and with the projection of problems in the relationship: politics-nature. The extraction of lithium in the Salar del Hombre Muerto dating back to 1997, to the present day, is analyzed. The role of the provincial government, the development of corporations and social resistance are examined from the divergent assessments and positions against this extractivist activity that reproduces the logic of Maldevelopment. The defense of water has become the foundation of social resistance to mining extractivism and Catamarca is no exception, for which the contributions of the Political Ecology of Water and categories will be considered as theoretical approaches that allow problematizing one of the elements in dispute: the valuation of water resources. In this line, the contributions of studies on mining extractivism, environmental conflicts, poor development and an introduction to the hydrosocial cycle are integrated, as theoretical approaches that allow problematizing one of the central elements in dispute: the protection of water.